Parental involvement in paediatric cancer treatment decisions - McKenna, K.; Collier, J.; Hewitt, M.; Blake, Holly (Wiley, 2010)
This study investigated parents' information needs and involvement in decision-making processes affecting the care of children diagnosed with cancer. Interviews and questionnaires were used to assess parental satisfaction in 50 mothers and 16 fathers responsible for 58 children in an English Paediatric Oncology Unit. Parents reported that doctors contributed almost twice as much to the decision-making process as they did, but parental satisfaction was positively correlated with the amount of information provided when giving informed consent. Satisfaction about their involvement in this process relied heavily upon the level of support received from others. Parents consenting to their child's involvement in non-randomised trials perceived themselves to be under greater pressure from others during the decision-making process while those whose children were further along the treatment trajectory were more uncertain about decisions previously made. Findings indicate that the accessibility, support, information and degree of control afforded to parents by healthcare professionals impacts upon their satisfaction with both the decision-making process and their confidence in the decisions thus made. Information and support tailored to parents' specific needs may therefore enhance satisfaction with clinical decision making and reassure parents about decisions made in the long-term interest of their child's health.